INTUSSUSCEPTIVE-LIKE ANGIOGENESIS IN HUMAN FETAL LUNG XENOGRAFTS: LINK WITH BRONCHOPULMONARY DYSPLASIA-ASSOCIATED MICROVASCULAR DYSANGIOGENESIS? - De Paepe, Monique E. (Exp Lung Res, 2015)
BACKGROUND: Human fetal lung xenografts display an unusual pattern of non-sprouting, plexus-forming angiogenesis that is reminiscent of the dysmorphic angioarchitecture described in bronchopulmonary dysplasia (BPD). The aim of this study was to determine the clinicopathological correlates, growth characteristics and molecular regulation of this aberrant form of graft angiogenesis. METHODS: Fetal lung xenografts, derived from 12 previable fetuses (15 to 22 weeks’ gestation) and engrafted in the renal subcapsular space of SCID-beige mice, were analyzed 4 weeks post-transplantation for morphology, vascularization, proliferative activity and gene expression. RESULTS: Focal plexus-forming angiogenesis (PFA) was observed in 60/230 (26%) of xenografts. PFA was characterized by a complex network of tortuous non-sprouting vascular structures with low endothelial proliferative activity, suggestive of intussusceptive-type angiogenesis. There was no correlation between the occurrence of PFA and gestational age or time interval between delivery and engraftment. PFA was preferentially localized in the relatively hypoxic central subcapsular area. Microarray analysis suggested altered expression of 15 genes in graft regions with PFA, of which 7 are known angiogenic/lymphangiogenic regulators and 5 are known hypoxia-inducible genes. qRT-PCR analysis confirmed significant upregulation of SULF2, IGF2 and HMOX1 in graft regions with PFA. CONCLUSION: These observations in human fetal lungs ex vivo suggest that postcanalicular lungs can switch from sprouting angiogenesis to an aberrant intussusceptive-type of angiogenesis that is highly reminiscent of BPD-associated dysangiogenesis. While circumstantial evidence suggests hypoxia may be implicated, the exact triggering mechanisms, molecular regulation and clinical implications of this angiogenic switch in preterm lungs in vivo remain to be determined.